A study of mediastinal tumours in a tertiary care centre: a retrospective study - Bomma, Kaladhar; Malempati, Amaresh R. (International Journal of Research in Medical Sciences, 2021)
Background: Recent advances in diagnostic and surgical techniques have brought major changes in the clinical presentation, diagnosis and the surgical management of mediastinal masses. Indian literature in this scenario is deficient, which our retrospective descriptive study aims to address. Methods: Details of patients operated for mediastinal masses from January 2007 November 2013 in two units at NIMS were collected. Clinical presentation, symptomatology, radiological/pathological findings, surgical approaches, intraoperative/immediate/intermediate post-operative results were evaluated and analysed. Results: Of the 75 patients, (48 males, range 10 years to 65 years) 2 deaths were due to complications following exacerbation of myasthenia gravis, and two patients died due to post-operative bleeding. Thymicneoplasms were the most common, followed by neurogenic tumours. Most common presentation was myasthenia gravis, followed by nonspecific back pain. 4% of patients had symptoms due to local compressive effects. Tumour was in the anterior mediastinum, middle and posterior mediastinum in 53, 16 and 6 cases respectively. Surgery done with a curative intent was through sternotomy (59), posterolateral thoracotomy (14), and combined sternotomy and cervical route (2). Residual tumour was present in 5 cases due to nerve involvement. Follow up was 98% (2 months to 6 years). 3 patients died of unrelated causes and one developed multiple lung metastases. 2 patients with neurogenic tumours developed recurrence. Conclusions: Inadequately optimized myasthenia patients and superior vena cava obstruction are poor prognostic factors. Complete excision may not be possible in neurogenic extension to spine even with concomitant neurosurgery. Neurological infiltration has a poorer prognosis.